Discourse On English Teaching Materials For Tour Guiding Based On Cultural Social Approach Analysis - Suparsa, I Nyoman; Suandi, I Nyoman; Warta, Ida Bagus; Seloka, Ida Bagus; Astawa, I Nengah (International Journal of Linguistics and Discourse Analytics, 2021)
Teaching English for specific purposes (ESP), which is in contrast with English for Academic purposes (EAP), has gained specially great attention since 1960’s. One of the examples of ESP is English for guiding. The main purpose of implementing English for guiding in some schools or collages is to give the students ability to communicate mainly orally so as to be able to fulfil the student’s need for his or her future carreer or job in tourism. In reality very often cultural misunderstandings which may pruduce fatal consequencies emerge among those who are involved in tourism industry. Due to this circumstance, inserting sosio-cultural aspects in the teacher’s languge teaching interaction is indeed beneficial. In this case, the role of the teacher to include edequate cultural aspects in language teaching, beside giving formal gramatical language forms, of course is highly worth considering. Teaching English for tourism industry is not regarded appropriate yet if sosio-cultural aspects are not adequately included. In other words, beside teaching the language forms, English teacher should incorporate sosio-cultural aspects into his interaction. Futhermore, materials for English for guiding is carefully selected which are based on carefull analysis of the course objectives. The implication of analysing teaching materilas intended for tour guide is expected that the outcomes of the institution or graduates are truly matched with the available jobs in job markets